2023
DOI: 10.3926/ic.2020
|View full text |Cite
|
Sign up to set email alerts
|

Does green innovation have an important role in the effect of board gender diversity and firm performance?

Abstract: Purpose: This research is motivated by the development of the debates on the role of board gender diversity and green innovation on firm performance. This study aims to investigate the mediating role of green innovation on the effect of board gender diversity and firm performance.Design/methodology/approach: This research employs regression analysis. The dataset using samples of 518 public listed companies on the Indonesia Stock Exchange over the period of 2017–2019.Findings: Based on 1,554 firm-year observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 78 publications
0
8
0
1
Order By: Relevance
“…In the context of Egyptian companies, gender diversity on the board of commissioners positively affects firm performance, as measured by TQ. While Molinero-Díez et al (2022) evidenced that women board of commissioners improve economic performance in companies in Germany, Mahsina and Agustia (2023) showed that board gender diversity has a positive effect on firm performance in companies that went public in Indonesia from 2017 to 2019. Assenga et al (2018) also found that gender diversity has a positive impact on the financial performance of listed firms in Tanzania.…”
Section: Women Board Of Commissioners (Wboc) and Firm Performance (Fp)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of Egyptian companies, gender diversity on the board of commissioners positively affects firm performance, as measured by TQ. While Molinero-Díez et al (2022) evidenced that women board of commissioners improve economic performance in companies in Germany, Mahsina and Agustia (2023) showed that board gender diversity has a positive effect on firm performance in companies that went public in Indonesia from 2017 to 2019. Assenga et al (2018) also found that gender diversity has a positive impact on the financial performance of listed firms in Tanzania.…”
Section: Women Board Of Commissioners (Wboc) and Firm Performance (Fp)mentioning
confidence: 99%
“…The sampling criteria are 1) companies listed on the Indonesia Stock Exchange from 2017 to 2021 from the non-financial sector, and 2) companies that provide a complete annual report to accommodate all research variables used. The non-financial sector serves as the criterion because the financial statements of non-financial companies with financial companies have different formats and components, thus reducing bias if included in the research sample (Mahsina & Agustia, 2023). However, since most of the data presented in the annual report are not available to cover our variables , the final sample includes 788 observations using a pooled unbalanced sample after purposive sampling.…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…Gender diversity in the board of directors is closely related to the company's ability to innovate (Nadeem et al, 2020). The presence of women on the board of directors brings different perspectives, experiences, and approaches to decision-making (Mahsina & Agustia, 2023). Likitapiwat et al, (2022) shows that more gender-diverse boards of directors tend to be better able to drive corporate innovation.…”
Section: Company Innovationmentioning
confidence: 99%
“…Unfortunately, the growing environmental issues are a result of the abundance of MSMEs (Firdausyi et al, 2023). This is due to their ignorance of the importance of environmental sustainability and because of their smaller size, their impact on the environment is not properly considered at regional and national levels (Mahsina & Agustia, 2023). Direct disposal of production waste without prior recycling can contaminate water and soil both within and outside the company environment (Firdausyi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Green innovation, namely innovation that takes into account environmental factors in the production process, can reduce MSME operational costs by saving energy, water, and raw materials. In the long term, this can increase profits and the competitiveness of MSMEs in the market (Mahsina & Agustia, 2023).…”
Section: Introductionmentioning
confidence: 99%